VERIFICATION TO THE RSG-GAS FUEL DISCHARGE BURN-UP USING SRAC2006 MODULE OF COREBN/HIST - Jati Susilo; Tagor Malem Sembiring; M Imron; Geni Rina Sunaryo (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2018)
For 30 years operation, some of the modifications to the RSG GAS core has been done, that are changes included the type of fuel from U3O8-Al to U3Si2-Al with the same density 2.96 gU/cc, the loading pattern of standard fuel elements/fuel control elements from 6/1 & 6/2 to 5/1 pattern, and in core fuel management calculation tool has been change from IAFUEL to BATAN-FUEL. To obtain an extension of the operating license for the next 10 years, the RSG-GAS Periodic Safety Assessment Document is need to prepared. According to the Regulatory Body Chairman Regulation No. 2 2015, RSG-GAS safety assessment should be done independently. As part of this assessment the fuel discharge burn-up must be estimated. In this research, to ensure that the misposition of fuel element in the core has not occurred, the investigation to the document operating report related the fuel placement has been done. Therefore, by using 78th to 93rd operation data, verify of the fuel discharge burn-up of the RSG-GAS has been performed by using SRAC2006 module of COREBN/HIST. In addition, the results of these calculations are also made comparative with the operating report data that is calculated by using BATAN-FUEL. Maximum fuel discharge burn-up (57.73% of U-235) was verified still under permissible value determined by the regulatory body (<60% of U-235). Maximum differences value between two computer codes was about 2.12 % of U-235 (3.80%) that is fuel at the B-7 position. Fuel discharge burn-up of RSG-GAS showed almost the same value for each the operation cycle, range of 1.52% of U-235. So it can be concluded that the RSG-GAS core operation over the last ten years was in good fuel management performance, in accordance with the design. BATAN-FUEL has been comformed well enough with COREBN/HIST. Keywords: Discharge Burn-Up, RSG-GAS, COREBN/HIST, BATAN-FUEL Verifikasi Terhadap Burn-Up Buang Bahan Bakar Teras RSG-GAS Menggunakan SRAC2006 Modul COREBN/HIST. Selama 30 tahun beroperasi, RSG-GAS telah mengalami perubahan modifikasi antara lain jenis bahan bakar dari U3O8-Al menjadi U3Si2-Al dengan kerapatan sama 2,96 gU/cc, pola pemuatan bahan bakar standar/elemen kendali dari pola 6/1 & 6/2 menjadi pola 5/1, dan alat perhitungan manajemen bahan bakar IAFUEL dengan BATAN-FUEL. Untuk memperoleh perpanjangan ijin operasi selama 10 tahun ke depan, maka perlu disiapkan dokumen Penilaian Keselamatan Berkala RSG-GAS. Berdasarkan PerKa BAPETEN No. 2 Tahun 2015, maka penilaian keselamatan RSG-GAS harus dilakukan secara independen. Salah satu parameter yang perlu diverifikasi adalah nilai bahan bakar buang. Dalam penelitian ini, dilakukan investigasi terhadap dokumen Laporan Operasi untuk memastikan bahwa tidak terjadi kesalahan penempatan bahan bakar. Selanjutnya, berdasarkan data siklus operasi teras ke 78 sampai dengan 93, dilakukan verifikasi nilai burn-up buang bahan bakar RSG-GAS dengan menggunakan SRAC2006 modul COREBN/HIST. Selain itu, hasil perhitungan tersebut juga dilakukan komparasi dengan data laporan operasi yaitu data hasil perhitungan menggunakan BATAN–FUEL. Fraksi bakar buang bahan bakar terbesar (57,73% U-235) terverivikasi masih di bawah nilai limit yang ditetapkan oleh badan pengawas (<60% U-235). Perbedaan hasil perhitungan terbesar kedua program computer sebesar 2,12% U-235 (3,80%) yaitu pada posisi B-7. Fluktuasi burn-up buang bahan bakar menunjukkan nilai yang hampir sama untuk tiap-tiap siklus operasi, jarak (range) sebesar 1,52% U-235. Sehingga dapat disimpulkan bahwa operasi teras RSG-GAS selama sepuluh tahun terakhir menunjukkan performa manajemen bahan bakar yang baik, sesuai desain. BATAN-FUEL telah terkonfirmasi cukup baik dengan COREBN/HIST. Kata kunci: Burn-up buang, RSG-GAS, COREBN/HIST, BATAN-FUEL